Quantum Markov chains on a Cayley tree - Mukhamedov, Farrukh (Universiti Putra Malaysia Press, 2011)
In the present paper we provode a construction of Quantum Markov chain on a Cayley tree. Moreover, we give a more concrete example of such chains, which is shift invariant and has clustering property.